Assessment of critical constructability activities among Malaysian building contractors - Saghatforoush, Ehsan; Hassim, Salihudin; Jaafar, Mohd Saleh; Abdul Kadir, Mohd Razali (EuroJournals Publishing, 2009)
After the primary researches on constructability issue which were implemented in United States, United Kingdom and Australia, more explorations were applied on that in order to assess this unique scientific fact in East Asian country of Malaysia. Based on the latest researches done on constructability concept in Malaysia, the most Critical Constructability Activities (CCAs) are defined according to amount of contractors’ participation in each activity and amount of gap between actual and potential effects of each of them on achieving the overall objectives of the construction projects with more cost and time savings and better quality which is the whole aim of a beneficial constructability activity. The present research aims to assess the current findings on CCAs in order to identify the types of contractors and projects which these CCAs are getting performed in and also the types of contracts is used in these CCAs. Finally it was found that there are some significant differences in amount of contractors’ involvement in CCAs among various considered independent variables. This study uses the former researches to help Malaysian construction stakeholders to find out the barriers of constructability implementation in building projects via giving more details on application of CCAs among different IVs.